2013
DOI: 10.2174/1874944501306010059
|View full text |Cite
|
Sign up to set email alerts
|

Neck, Wrist and Back Pain Among Solid Waste Collectors: Case Study of a Ghanaian Waste Management Company

Abstract: Prevalence of Neck Wrist and Back pain (NWBP) among solid waste collectors (SWCs) of Zoom Lion Company (ZL) is 44.7%, 48.2% and 73.5% respectively, irrespective of pre-existing periodic pains. It was established that 42/340 (12.4%) SWCs of ZL had neck pain before joining ZL, whilst 298/340 (87.6%) developed neck pain after joining ZL (P-value = 0.001). Again, 32/340 (9.4%) had wrist pain before joining ZL, whilst 308/340 (90.6%) developed wrist pain after joining ZL (P-value = 0.000). Finally, SWCs who had bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 14 publications
8
16
1
Order By: Relevance
“…In the absence of any studies on MSDs among the street sweepers, the results of the present study are comparable with the other studies conducted among the solid waste workers except in the case of knee and ankle disorders 34 11 27 28 This may be because the street sweepers are not engaged in lifting heavy loads continuously or for carrying them for long duration, as a result of which they do not put as much pressure on the knees and ankles as those engaged in solid waste collection. A cross-sectional study conducted in Iran among 217 municipal solid waste workers showed a higher prevalence of the MSDs for lower back (45%), knees (29%), shoulders (24%), upper back (23%) and neck (22%) as compared with the comparison group 5.…”
Section: Discussionsupporting
confidence: 87%
“…In the absence of any studies on MSDs among the street sweepers, the results of the present study are comparable with the other studies conducted among the solid waste workers except in the case of knee and ankle disorders 34 11 27 28 This may be because the street sweepers are not engaged in lifting heavy loads continuously or for carrying them for long duration, as a result of which they do not put as much pressure on the knees and ankles as those engaged in solid waste collection. A cross-sectional study conducted in Iran among 217 municipal solid waste workers showed a higher prevalence of the MSDs for lower back (45%), knees (29%), shoulders (24%), upper back (23%) and neck (22%) as compared with the comparison group 5.…”
Section: Discussionsupporting
confidence: 87%
“…Low back disorders were defined differently in most of the articles; this may be linked to the variability in reported prevalence rates. All reviewed articles reported 12-month prevalence; prevalence rates varied widely from 16% [23] to 74% [29]. The variation in LBD prevalence identified in the present study demonstrates a common issue in LBD research: differences in study design; methodological approach [32]; and LBD case definition.…”
Section: Lbd Prevalence Among Waste Workersmentioning
confidence: 63%
“…The quality of the methodological strategies used may also contribute to the differences in the reported prevalence. A study by Norman et al [29] showed that, cross-sectional studies, self-reported data, and bias in recall can under or overestimate the prevalence of LBD among waste workers. Given the variation in data collection methods, tools, and case definitions, it is not unexpected to see a range of prevalence among the 13 studies Though the included articles focused on a similar occupational group, they did differ in their selection of the study sample, their mode of collecting data, and possibly cultural perceptions of pain across geographic regions.…”
Section: Lbd Prevalence Among Waste Workersmentioning
confidence: 99%
See 2 more Smart Citations